(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
A 27 cast carbon steel, which was used in induced draft fan blades of Nasiriyah thermal electricity station was chose to actualize the aim of this paper by studying the effect of shot peening time on dry and corrosion fatigue life. .Many specimens from the metal choice for tensile and fatigue tests were equipped according to ASTM (E8/E8M-09) some of preparing specimens were subjected to shot peening by steel ball in diameter 2.25 mm for different time (10, 20, 30) minute. Hardness, residual stress, surface roughness , dry fatigue and corrosion fatigue were tested. The result showed an improvement in the tensile strength for shot peening comparing with the base metal. The tensile strength of the shot peening metal at 20 minute was higher than the tensile strength of the shot peening at 10,30 minute. Also shot peening contributed in improvement fatigue life but the best time was 20 minute and this improvement witness decay in fatigue life by corrosion fatigue test due the effect of environment in addition of cyclic loads.